1997
DOI: 10.1016/s0014-5793(97)00405-5
|View full text |Cite
|
Sign up to set email alerts
|

Xanthones as antimalarial agents; studies of a possible mode of action

Abstract: We recently demonstrated that 2,3,4,5,6-pentahydroxyxanthone (X5) inhibits the in vitro growth of both chloroquine-sensitive and multidrug-resistant strains of P. falcipamm.To study the molecular basis of its antimalarial action, we tested X5 and selected hydroxyxanthone analogs as inhibitors of in vitro heme polymerization in a low ionic strength phosphate solution at mildly acidic pH. We found that addition of 1 Eq. of X5 resulted in complete inhibition of polymerization in this system whereas addition of up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 24 publications
5
71
0
5
Order By: Relevance
“…In contrast, the only signifi- cant correlations for MB were with CQ, AQ, and PIP in P. falciparum, a pattern similar to that observed in previous studies (22,24). MB's parasitocidal activity is postulated to be mediated by the inhibition of heme polymerization (39,41) and glutathione reductase in P. falciparum (42,43). Assuming a similar mode of cytotoxicity in P. vivax, the contrasting correlation most likely indicates differences in drug uptake and partition between the two species.…”
Section: Discussionsupporting
confidence: 79%
“…In contrast, the only signifi- cant correlations for MB were with CQ, AQ, and PIP in P. falciparum, a pattern similar to that observed in previous studies (22,24). MB's parasitocidal activity is postulated to be mediated by the inhibition of heme polymerization (39,41) and glutathione reductase in P. falciparum (42,43). Assuming a similar mode of cytotoxicity in P. vivax, the contrasting correlation most likely indicates differences in drug uptake and partition between the two species.…”
Section: Discussionsupporting
confidence: 79%
“…The ability of the EA derivatives to interfere with heme aggregation was determined in 20 mM sodium phosphate (pH 5.2) as described by Ignatushchenko et al (19). A 10 mM stock solution of hemin chloride in 0.1 M NaOH was prepared freshly and incubated at 37°C for at least 1 h prior to use.…”
Section: Drugs and Chemicalsmentioning
confidence: 99%
“…We have demonstrated that selected hydroxyxanthones form soluble complexes with heme and prevent the precipitation of heme in aqueous solution under the mildly acidic conditions of the digestive vacuole at pH 5.2 (14). In a recent study of the interaction between heme and 4,5-dihydroxyxanthone, a model that features carbonyl-iron coordination, -stacking of the coplanar aromatic molecules, and hydrogen bonding between the drug's hydroxyl substituents and the propionate side chains of heme was found to be consistent with the proton nuclear magnetic resonance (NMR) data (17).…”
mentioning
confidence: 99%